The digital readiness of future physicians: nurturing the post-pandemic medical education - Marta Marsilio; Valeria Calcaterra; Gabriele Infante; Martina Pisarra; Gianvincenzo Zuccotti (BMC, 2024)
Abstract Background The COVID-19 pandemic has accelerated the integration of digital technologies in the healthcare sector. Telemedicine has notably emerged as a significant tool, offering a range of benefits. However, various barriers, such as healthcare professionals' insufficient technological skills and competencies, can hinder its effective implementation. Scholars have examined the readiness of future physicians, with some studies exploring their readiness before or during the COVID-19 crisis. There is, however, a noteable gap in the literature concerning the post-pandemic period. This study aims to identify gaps in current medical education programs by examining two primary aspects: (1) technical readiness (encompassing general and health-related digital competencies) and (2) behavioural readiness, which includes prior experiences and future intentions related to telemedicine education and implementation among medical students and residents. Methods A cross-sectional study was conducted using a web-based questionnaire administered to medical students and residents at a major Northern Italian university. The survey responses were analyzed to ascertain whether their distributions varied across demographic variables such as gender and level of education. Results The most commonly owned technologies were laptops and smartphones, with smartphones perceived as the easiest to use, while desktop computers presented more challenges. Approximately 38% of respondents expressed apprehension about applying digital health information in decision-making processes. There was a significant lack of both personal and academic experience, with only 16% of students and residents having used telemedicine in a university setting. Despite this, 83% of participants expressed a desire for training in telemedicine, and 81% were open to experimenting with it during their academic journey. Moreover, 76% of respondents expressed interest in incorporating telemedicine into their future clinical practice. Conclusions This study highlights the need for medical students and residents to receive specific education in digital health and telemedicine. Introducing curricula and courses in this domain is critical to addressing the challenges of digital healthcare.